2019
DOI: 10.1186/s12879-019-4041-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human T-lymphotropic virus 2 (HTLV-2) infection in villages of the Xikrin tribe (Kayapo), Brazilian Amazon region

Abstract: Background Studies have shown that the human T-lymphotropic virus 2 (HTLV-2) is endemic in several indigenous populations of the Brazilian Amazon and molecular analyses have shown the exclusive presence of HTLV-2 subtype 2c among the indigenous groups of this geographical region. Methods The present study characterizes the prevalence of HTLV-2 infection in three new villages of the Xikrin tribe, in the Kayapo group, according to their distribution by sex and age. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 34 publications
6
42
2
Order By: Relevance
“…The initial figures indicated that the prevalence rates measured by immunoenzymatic assays ranged from 3.6% to more than 30% for HTLV-1, mostly among Indians populations [84,85], that the rate was 0.91% among those undergoing blood donation screening [100]. A large distribution of HTLV-2 was shown among Indians communities not only in the State of Para but also in the Amazon area of Brazil, reaching confirmed prevalence rates of more than 40% [6,51,56,63] among some Indian communities and the detection of a new molecular subtype (HTLV-2c) that was soon also described in urban areas outside of the ARB [6,33,50,51,116]. Prevalence studies also provide interesting information, such as the description of HTLV-2b among blood donors in Belém, which stresses the need for ongoing molecular epidemiology investigations [116].…”
Section: Epidemiological Data Of Htlv-1 and Htlv-2 In The Amazon Regimentioning
confidence: 98%
See 3 more Smart Citations
“…The initial figures indicated that the prevalence rates measured by immunoenzymatic assays ranged from 3.6% to more than 30% for HTLV-1, mostly among Indians populations [84,85], that the rate was 0.91% among those undergoing blood donation screening [100]. A large distribution of HTLV-2 was shown among Indians communities not only in the State of Para but also in the Amazon area of Brazil, reaching confirmed prevalence rates of more than 40% [6,51,56,63] among some Indian communities and the detection of a new molecular subtype (HTLV-2c) that was soon also described in urban areas outside of the ARB [6,33,50,51,116]. Prevalence studies also provide interesting information, such as the description of HTLV-2b among blood donors in Belém, which stresses the need for ongoing molecular epidemiology investigations [116].…”
Section: Epidemiological Data Of Htlv-1 and Htlv-2 In The Amazon Regimentioning
confidence: 98%
“…Human infections by HTLV in the Amazon region of Brazil have been recorded by several studies involving blood donors [82,[98][99][100][101][102], pregnant women [103][104][105][106], urban familial aggregates [42] and native Indians [6,56] (Fig. 1).…”
Section: Epidemiological Data Of Htlv-1 and Htlv-2 In The Amazon Regimentioning
confidence: 99%
See 2 more Smart Citations
“…This information is useful for detecting the occurrence and frequency of the viruses in order to determine the pathways through which the virus moves and the possible routes for future spread. HTLV-1 and HTLV-2 are largely distributed around the world ( Gessain and Cassar 2012 ; Braço et al. 2019 ; Li et al.…”
Section: Introductionmentioning
confidence: 99%